223k views
0 votes
1) Solve for x :3(2x - 5)-x--76x+3)

1 Answer

2 votes

You have the following equation:

3(2x-5)-x = -7(x+3)

In order to solve the previous equation, you proceed as follow:

3(2x-5)-x = -7(x+3) apply distribution property to eliminate parenthesis

(3)(2x) + (3)(-5) - x = (-7)(x) + (-7)(3)

6x - 15 - x = -7x - 21 simplify like terms left side

5x - 15 = -7x - 21 add 7x both sides

5x + 7x - 15 = - 21

12x - 15 = -21 add 15 both sides

12x = -21 + 15

12x = - 6 divide by 12 both sides

x = - 6/12

x = -1/2

Hence, the solution for x in the given equation is x = -1/2

User Nisetama
by
4.9k points